Mary McLeod Bethune the Pan-Africanist - Preston, Ashley Robertson (University Press of Florida, 2023)
"Broadening the familiar view of Mary McLeod Bethune as an advocate for racial and gender equality within the United States, this book highlights Bethune's global activism and her connections throughout the African diaspora"--